A pre and post intervention study to reduce unnecessary urinary catheter use on general internal medicine wards of a large academic health science center - Wooller, Krista R.; Backman, Chantal; Gupta, Shipa; Jennings, Alison; Hasimja-Saraqini, Delvina; Forster, Alan J. (Université d'Ottawa | University of Ottawa, 2018)
Urinary catheters are a common medical intervention, yet they can also be associated with harmful adverse events such as infection, urinary tract trauma, delirium and patient discomfort. The purpose of this study was to describe the use of the SafetyLEAP program to drive improvement efforts, and specifically to reduce the use of urinary catheters on general internal medicine wards.
Keywords: Patient safety; Quality improvement; Urinary catheter; Aged; Canada; Catheter-Related Infections; Cross Infection; Female; Humans; Male; Patient Safety; Quality Improvement; Unnecessary Procedures; Urinary Catheterization; Urinary Tract Infections; Academic Medical Centers; Internal Medicine; Patients' Rooms